Analisis Bibliometrik: Tren Penelitian Kesulitan Keuangan di Indonesia - Djumaiyah Djumaiyah; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
There are many academic publications on the topic of financial hardship. Financial problems themselves are a situation that must be avoided by business people in a corporate organization. In addition, financial difficulties are a situation that is not only detrimental to the company but also to investors. It is important to know the condition of the company in order to avoid financial reporting, so it is very important to carry out research regarding this matter. The purpose of this article is to provide information regarding published research related to financial reporting that occurred in the period 2017 – 2023. The method used in this research is to identify journals using Harzing's Publish-or-Perish software, as well as bibliometric analysis using using the VOSviewer technique. The research results show that there are 998 publications with 9294 citations and 1327 citations per year that discuss financial issues. Referring to the results of the VOSviewer analysis, there are five large clusters. This article will provide information related to research topics that have not been widely conducted so that it can provide benefits to stakeholders who may need it for further research purposes.